Juridical Review of Actio Pauliana Against Bankrupt Boedal Becoming The Object Of Liability - Hamonangan Turnip, M.O. Saut (JUSTISI, 2024)
The Bankruptcy and Postponement of Debt Payment Obligations Act of 2004 regulates the bankruptcy process, which involves the conversion of a debtor's personal assets into bankrupt assets. The court appoints a curator and a supervising judge to oversee all of the insolvent estate's assets. The curator may come across legal measures initiated by the debtor against the bankrupt assets during this procedure that might be harmful to creditors. Paulina's action is what the curator can do in these circumstances to ask the court to dismiss these legal actions. The purpose of this study is to comprehend how Paulina's intervention supports the rights of creditors, particularly with regard to mortgage rights.The study used normative legal research and conducted descriptive and qualitative analyses of both primary and secondary data. The findings revealed that Paulina's action can be used to protect the mortgage rights of creditors, provided that certain dejure elements are met. The study highlights the importance of consistency and synchronization of decisions based on the principles and norms of bankruptcy law to achieve legal harmonization.In conclusion, Paulina's action plays a critical role in safeguarding the interests of creditors in bankruptcy cases, particularly regarding mortgage rights. It empowers the curator to cancel legal actions that could harm the creditors and promotes legal harmonization. This study underscores the need for consistent and coherent application of bankruptcy laws to ensure the equitable treatment of all parties involved. Keywords : Actio Paulina, Legal Action, Bankruptcy Law